(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Pilonidal sinus is one of the most common sinuses seen in general surgical practice and usually seen in the natal cleft. Postoperative wound complications have always been the main cause of concern followed by the risk of recurrence in the surgical treatment of the pilonidal sinus disease. Various techniques evolved so far mainly aimed at solving these problems. This clinical study conducted to discuss the results of elliptical rotational flap in chronic pilonidal sinus. Objective:To assess the outcome of patients operated by rotational flap procedure in chronic pilonidal disease in term of healing time, complications and recurrence rate. Methods: The study was conducted in two different places from December 2007 till April 2011. Eighty two patients with chronic pilonidal sinus were treated by rotation flap. The setting was in two different places, at Nizwa General Hospital, Sultanate of Oman and from Al-Imamain Al-Kadhemain Medical City, Baghdad. Evaluation of operative and post-operative results, complications and recurrence in addition to demographic data. Results:Out of 82 Patients included in study, 2 cases (2.4%) failed to heal due to partial necrosis of the flap and underwent redo surgery, while 80 patients (97.4%) were cured completely and no further surgery was needed. Eighteen patients (22%) went home in the end of same day and the rest (78%) discharged in second day. Forty six Patients (56%) had dry dressing till suture removed after 8 days, while 20 Patients (24.4%) continued to discharge serosangunious fluid and spent more than 10 days to heal. Eight Patients (9.8%) developed seroma needed further time to becomes dry and the last 6 Patients (7.3%) developed wound infection and treated by proper antibiotics and surgical drainage in some case. conclusion:Flap procedures may be promising especially in complex and recurrent pilonidal diseases as it is simple to be done and carry low recurrence rate and relatively shorter hospital stay in comparison to other surgical procedure Keywords :Chronic pilonidal sinus, elliptical rotation flap.